Implementation of problem-based learning (PBL) with virtual laboratory to improve students' critical thinking and achievement. (February 2020) - Serungke, M; Muhibbuddin,; Suhrawardi,
Abstract: Critical thinking skill is an important tool used by students to solve the common problems either internal problem or problems that are found in school. This research aimed at indicating the influence of problem-based learning model implementation accompanied with the virtual laboratory to students' critical thinking skills and learning achievement. The method was a true experiment and the sample was taken by using the true experiment technique, where grade ten-two class was selected as the experimental class and grade ten-three class as control class. Each of the classes consisted of 30 students. The experimental class was taught using PBL accompanied by the virtual laboratory. The collected data were analyzed by studying the comparison of improvement from a result of pretest and N-Gain and continued by using the t-test. The findings showed that there were no differences between students' average scores between the experimental class and control class. N-Gain showed the real differences between the two classes. Overall, N-Gain for critical thinking skill function analysis revealed better results in experimental class than control class. It can be concluded that problem-based learning model implementation accompanied with virtual laboratory effectively increases students' critical thinking skills and learning achievement.